A FATHER SAYS TO HIS SON,7 YEARS AGO,I WAS 7 TIMES AL OLD AS YOU WERE AND AFTER 3 YEARS I WILL BE 3 TIMES AL OLD AS YOU WILL BE.FIND THEIR PRESENT AGES.
khushirani803:
I know answer but I am not getting chance
Answers
Answered by
9
Hello Mate !!
Here is your solution :
Imagine you are father and you are telling to your son.
Let your age is x and the age of your son is y.
What did you say ?
7 years ago,I was 7times as old as you.
So,
Your age before 7 years = x - 7 years.
The age of your son at that time = y - 7 years.
Now, it is given that you were 7 times older than him.
So, if we shall multiply by 7 in your son's age then we would get your age.
=> ( x - 7 yrs ) = 7 ( y - 7 yrs )
=> x - 7 yrs = 7y - 49 yrs
=> x - 7y = -49 yrs + 7 yrs
=> x - 7y = -42 yrs
=> 42 yrs = 7y - x ------ ( 1 )
Now, what did you say about future ?
You will be 3 times as old as he will be after 3 years.
Now,
Your age after 3 years = x + 3 years.
Age of your son after 3 years = y + 3 years.
Now, according to question , you will be 3 times older than him.
So, if we multiply by 3 to his age after 3 yrs then we will get your age.
=> x + 3 yrs = 3 ( y + 3 yrs )
=> x + 3 yrs = 3y + 9 yrs
=> x - 3y = 9 yrs - 3 yrs
=> x - 3y = 6 yrs ------------ ( 2 )
By adding ( 1 ) and ( 2 ),
=> 7y - x + x - 3y = 42 yrs + 6 yrs
=> 4y = 48 yrs
=> y = 48 yrs ÷ 4
=> y = 12 yrs.
By substituting the value of y in ( 1 ),
=> 42 yrs = 7y - x
=> 42 yrs = 7 ( 12 yrs ) - x
=> 42 yrs = 84 yrs - x
=> 42 yrs - 84 yrs = -x
=> -42 yrs = -x
=> x = 42 yrs.
Hence, age of that person is 42 yrs and age of his son is 12 yrs.
================================
Hope it helps !
^_^
Here is your solution :
Imagine you are father and you are telling to your son.
Let your age is x and the age of your son is y.
What did you say ?
7 years ago,I was 7times as old as you.
So,
Your age before 7 years = x - 7 years.
The age of your son at that time = y - 7 years.
Now, it is given that you were 7 times older than him.
So, if we shall multiply by 7 in your son's age then we would get your age.
=> ( x - 7 yrs ) = 7 ( y - 7 yrs )
=> x - 7 yrs = 7y - 49 yrs
=> x - 7y = -49 yrs + 7 yrs
=> x - 7y = -42 yrs
=> 42 yrs = 7y - x ------ ( 1 )
Now, what did you say about future ?
You will be 3 times as old as he will be after 3 years.
Now,
Your age after 3 years = x + 3 years.
Age of your son after 3 years = y + 3 years.
Now, according to question , you will be 3 times older than him.
So, if we multiply by 3 to his age after 3 yrs then we will get your age.
=> x + 3 yrs = 3 ( y + 3 yrs )
=> x + 3 yrs = 3y + 9 yrs
=> x - 3y = 9 yrs - 3 yrs
=> x - 3y = 6 yrs ------------ ( 2 )
By adding ( 1 ) and ( 2 ),
=> 7y - x + x - 3y = 42 yrs + 6 yrs
=> 4y = 48 yrs
=> y = 48 yrs ÷ 4
=> y = 12 yrs.
By substituting the value of y in ( 1 ),
=> 42 yrs = 7y - x
=> 42 yrs = 7 ( 12 yrs ) - x
=> 42 yrs = 84 yrs - x
=> 42 yrs - 84 yrs = -x
=> -42 yrs = -x
=> x = 42 yrs.
Hence, age of that person is 42 yrs and age of his son is 12 yrs.
================================
Hope it helps !
^_^
Answered by
2
=> ( x - 7 yrs ) = 7 ( y - 7 yrs )
=> x - 7 yrs = 7y - 49 yrs
=> x - 7y = -49 yrs + 7 yrs
=> x - 7y = -42 yrs
=> 42 yrs = 7y - x ------ ( 1 )
=> x + 3 yrs = 3 ( y + 3 yrs )
=> x + 3 yrs = 3y + 9 yrs
=> x - 3y = 9 yrs - 3 yrs
=> x - 3y = 6 yrs ------------ ( 2 )
By adding ( 1 ) and ( 2 ),
=> 7y - x + x - 3y = 42 yrs + 6 yrs
=> 4y = 48 yrs
=> y = 48 yrs ÷ 4
=> y = 12 yrs.
By substituting the value of y in ( 1 ),
=> 42 yrs = 7y - x
=> 42 yrs = 7 ( 12 yrs ) - x
=> 42 yrs = 84 yrs - x
=> 42 yrs - 84 yrs = -x
=> x = 42 yrs.
Similar questions